Stabilization of mesophilic Allochromatium vinosum cytochrome c′ through specific mutations modeled by a thermophilic homologue. Issue 2 (1st February 2018) - Yamane-Koshizawa, Daisuke; Fujii, Sotaro; Maruno, Takahiro; Kobayashi, Yuji; Yamanaka, Masaru; Wakai, Satoshi; Sambongi, Yoshihiro
Abstract: AVCP cytochrome c ′ from mesophilic Allochromatium vinosum exhibits lower stability than a thermophilic counterpart, Hydrogenophilus thermoluteolus cytochrome c ′ (PHCP), in which the six specific amino acid residues that are not conserved in AVCP are responsible for its stability. Here we measured the stability of AVCP variants carrying these specific residues instead of the original AVCP ones. Among the six single AVCP variants, all of which formed a dimeric structure similar to that of the wild-type, three were successfully stabilized compared with the wild-type, while one showed lower stability than the wild-type. In addition, the most stabilized and destabilized AVCP variants could bind CO, similar to the wild-type. These results indicated that mesophilic AVCP could be stabilized through specific three mutations modeled by the thermophilic counterpart, PHCP, without changing the CO binding ability. Abstract: : Mesophilic AVCP could be stabilized through mutations.